Styles of responding to changes of employees and organisational justice - Fofanova, Galina A.; Sorokina, Anastasia A. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
Spontaneous and planned changes in the internal and external environment of an organisation invariably pose a challenge to its functioning and efficiency, since the success of their implementation depends not only on material resources, but also on the human factor. One of the variables that describe the potential for employees to accept innovations is the style of responding to changes – a kind of human adaptation mechanism to a changing environment, including both the characteristics of the situation and the individual characteristics of a person. Organisational justice, as an employee’s assessment of the integrity of intra-organisational relationships in an organisational context, is another important variable. It has a powerful motivational potential. This article is devoted to the relationship between these two phenomena and the description of the results of empirical study.
Keywords: organisational justice; styles of responding to changes of employees; employees; organisation leaders; holding company; Belarus